'Customers were not objects to suck blood from': Social relations in UK retail banks under changing performance management systems. Issue 5 (9th August 2019) - Laaser, Knut
Abstract: Utilising an analytical framework informed by a moral economy approach, this article examines the social relationships between bank workers and customers in the context of changing performance management. Informed by 46 in‐depth interviews with branch workers and branch managers from UK banks, this article focusses on the interplay of the pressures arising from an intensified and all‐encompassing performance management system and bank workers lay morality. The article seeks to analyse why one group of bank workers engages with customers in a primarily instrumental manner, while another group tends to mediate and engage in oppositional practices which aim to avoid such an instrumentalisation. The article argues that moral economy gives voice to the agency of workers and the critical concerns of the social, economic and moral consequences of market‐driven and purely profit‐oriented workplace regimes.